2017
DOI: 10.1080/21650373.2017.1411297
|View full text |Cite
|
Sign up to set email alerts
|

Crack sealing capacity in chloride-rich environments of mortars containing different cement substitutes and crystalline admixtures

Abstract: This paper presents the results of a preliminary study aimed at assessing the crack sealing capacity in chloride environments of different concrete mixtures, incorporating supplementary cementitious materials as well as self healing enhancing crystalline admixtures. For each addition, also including pulverized fuel ash and silica fume, different contents were taken into consideration. Cylinder specimens were pre-cracked in splitting up to three different crack opening ranges, simulating different service condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 32 publications
4
34
0
Order By: Relevance
“…Improved performance under exposure to artificially replicated seawater (both submersion and wet–dry cycles) was also reported by Borg et al as well as by Cuenca et al who also hypothesized a contribution of crystalline admixtures to chloride binding.…”
Section: Autogenous and Nonencapsulated Autonomous Self‐healingsupporting
confidence: 72%
“…Improved performance under exposure to artificially replicated seawater (both submersion and wet–dry cycles) was also reported by Borg et al as well as by Cuenca et al who also hypothesized a contribution of crystalline admixtures to chloride binding.…”
Section: Autogenous and Nonencapsulated Autonomous Self‐healingsupporting
confidence: 72%
“…For instance, for a specimen without crystalline admixtures immersed in 16.5% NaCl solution with a chloride content of 0.51%, 0.75%, and 0.85% were detected after 1, 3, and 6 months of exposure time, respectively. According to previous studies (Guinee et al 2011;Borg et al 2018), it is well-known that the chloride ingress close to the exposed surface is usually not diffusion controlled, indeed is part of the convection zone. In fact, some researchers have detected an increased calcium leaching on the surface in contact with the exposure solution that results into a reduction of the chloride binding capacity (Álava et al 2016;Elakneswaran et al 2010).…”
Section: Chemical Titration Tests: Chloride Penetration Profilesmentioning
confidence: 97%
“…It was observed that self-healing led to a reduction of chloride content for both mixes, but the chloride content in the specimens having the self-healing agent was lower. Borg et al (2018) studied the crack sealing capacity of mortars containing supplementary cementitious materials (fuel ash and silica fume) or crystalline admixture (same as used in this research) in chloriderich environments. They observed that sea water may lead to an enhancement of the self-healing capacity of mortars with respect to distilled water, especially for higher chloride contents (16.5% NaCl aqueous solution).…”
Section: Introductionmentioning
confidence: 99%
“…Research on secondary crystallization in cement composites has previously been dealing with the sealing of pore structures and sealing cracks. e benefits of utilisation of crystalline admixtures are well demonstrated in previously published studies [25][26][27][28][29][30]: however, improving the properties of concrete remains an important task even today [19]. Improving the durability of cementitious composites helps extend their longevity, thereby reducing repair costs associated with moisture damage of concrete structures [31].…”
Section: Introductionmentioning
confidence: 89%